2013
DOI: 10.1017/s1751731113001626
|View full text |Cite
|
Sign up to set email alerts
|

Using eye temperature and heart rate for stress assessment in young horses competing in jumping competitions and its possible influence on sport performance

Abstract: The aims of this study were, first, to evaluate eye temperature (ET) with infrared thermography and heart rate (HR) to measure stress in horses during show jumping competitions and their relationship with competition results, and second, to evaluate the influence of different extrinsic and intrinsic factors of the horse on the stress measurements analysed. One hundred and seventy-three Spanish Sport Horses were analysed for ET and HR, and these measurements were taken 3 h before the competition, just after and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 42 publications
(61 reference statements)
4
82
2
4
Order By: Relevance
“…Similar results were found by Hall et al (2010) who found a higher eye temperature in horses lunged with the Pessoa training aid (held responsible for increasing the stress during training) than horses without. Bartolomé et al (2013) were able to demonstrate a correlation between an increase in heart rate and eye temperature after jumping competitions. Cook et al (2001) investigated the underlying causes of increase in eye temperature in horses and found that it was correlated to activation of the hypothalamicepituitaryeadrenal axis.…”
Section: Introductionmentioning
confidence: 90%
“…Similar results were found by Hall et al (2010) who found a higher eye temperature in horses lunged with the Pessoa training aid (held responsible for increasing the stress during training) than horses without. Bartolomé et al (2013) were able to demonstrate a correlation between an increase in heart rate and eye temperature after jumping competitions. Cook et al (2001) investigated the underlying causes of increase in eye temperature in horses and found that it was correlated to activation of the hypothalamicepituitaryeadrenal axis.…”
Section: Introductionmentioning
confidence: 90%
“…Changes in eye temperature in relation to stressful or painful procedures were found in horses [3,10], cattle [8,9,21,22], and elk [23], although changes were not always in the same direction.…”
Section: Introductionmentioning
confidence: 95%
“…[6,7]) and thermoregulation analysis [5]. In animal welfare science, its applicability in the measurement of physiological stress responses has been explored, such as via eye temperature in cattle [8,9] and horses [10], ear temperature in rabbits [11], and temperature of the comb and wattle in chickens [12], adding to the more conventional methods of stress monitoring in non-human animals (including body posture, heart rate, heart rate variability, and cortisol concentrations in saliva, plasma and urine [13][14][15]). Recently, thermography has also been used in the assessment of positive affective states in animals [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…IR thermography has been used in recent years as a non-invasive method in many animal species as well as in humans. The method is a useful tool in predicting increases in local (Rainwater-Lovett et al, 2009) or systemic body temperature (e.g., Johnson et al, 2011), which can serve as a tool to assess stress in dairy cows (Stewart et al, 2007) and sport horses (Bartolomé et al, 2013) and to predict cow oestrus (Talukder et al, 2014). Furthermore, Kammersgaard et al (2013) showed the utility of IR thermography in † E-mail: ghoffmann@atb-potsdam.de Animal (2016), 10:9, pp 1542-1546 © The Animal Consortium 2015 doi:10.1017/S1751731115001354 animal 1542 evaluating the thermal status of neonatal pigs.…”
mentioning
confidence: 99%